The Existence Of the Betel Leaf (Piper betle L.) is in the Tasawuf Prespective - Resty Rahmatika; Djoko Hartono; Hartoyo (http://jagadalimussirry.com/, 2019)
Plants are one of the richest natural resources in Indonesia and contain active chemicals. These plants have the potential to become raw materials for traditional medicine. One of them is betel plant. The use of Betel leaves, especially in Java, is generally accompanied by special conditions or criteria, namely: betel leaf which 'meets ros-e'. 'Ros' comes from the Javanese language which means vein, in this case it is a vein of leaves. 'Temu' comes from the Javanese language which means to meet, meet. Betel rose meeting is betel which leaves veins (lateral nerves) meet theposition of the segment; so that the shape is symmetrical. Meanwhile, phytochemical laboratory testresults for total flavonoid content of betel leaves and non-temurose leaves were 53,522 and 43,041 ppm. These values include high levels (> 50 ppm) and moderate levels (between> 10 - 50 ppm). The higher the level of flavonoids, the more likely the antioxidant potential will be. In the implementation of riyadhoh, making betel leaves meet rose as a medium as a form of philosophy that is betel or tell me means ngangsu kaweruh (studying), whereas meet rose can be interpreted as meeting taste.